Caves - Beckerman, Nell Cross, 1973- (Orchard Books, an imprint of Scholastic Inc., 2022)
"A masterful exploration of one of nature's most curious ecosystems, Caves is a magical journey into subterranean wonders perfect for fans of Jason Chin. Using evocative storytelling, Nell Cross Beckerman urges children to explore one of nature's most curious ecosystems. Dramatic, poetic language guides kids through different caves around the world while nonfiction text allows for deeper understanding"--